2018
DOI: 10.1371/journal.pone.0202221
|View full text |Cite
|
Sign up to set email alerts
|

Prediction of the caved rock zones’ scope induced by caving mining method

Abstract: Critical medium column theory has typically been used to predict the scope of caved rock zone (CRZ) caused by caving mining method. It is essential to understand the distribution laws of lateral pressure induced by caving mining method with different dipping angles. In this study, a self-designed scaled physical model was used to investigate the distribution laws with angles ranging from 80° to 90°, and ore drawing was employed in experiments to simulate caving mining method. The experimental results indicated… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
10

Relationship

4
6

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 26 publications
(22 reference statements)
0
7
0
Order By: Relevance
“…In this study, a new standpoint was proposed that the distribution laws could be divided into three parts, and then the lateral pressure increased exponentially with increasing depth of granular media. Ren et al [35] and He et al [36] reported the distribution laws of lateral pressure from different orebody dip conditions, which seemed consistent with the scope of drawing influencing region, but to a certain extent had its variation on the upper descending zone and the central growth area. ese abovementioned results are under the invariable width of orebody, and the vibration of blasting is not considered; further studies are essential to improve this simple description to the more comprehensive results of complex gravity flow encountered in actual mines.…”
Section: Discussionmentioning
confidence: 59%
“…In this study, a new standpoint was proposed that the distribution laws could be divided into three parts, and then the lateral pressure increased exponentially with increasing depth of granular media. Ren et al [35] and He et al [36] reported the distribution laws of lateral pressure from different orebody dip conditions, which seemed consistent with the scope of drawing influencing region, but to a certain extent had its variation on the upper descending zone and the central growth area. ese abovementioned results are under the invariable width of orebody, and the vibration of blasting is not considered; further studies are essential to improve this simple description to the more comprehensive results of complex gravity flow encountered in actual mines.…”
Section: Discussionmentioning
confidence: 59%
“…Hence, numerous literatures have demonstrated such contribution; Laubscher [13] proposed an empirical solution to describe the effect of the density and height of caved rocks. To describe the stress from caved rocks to the surrounding rocks in a confined space, Ren et al [25] conduct the scaled laboratory tests, and the results reveal this stress matches the solution for granular materials by Janssen [26]:…”
Section: Impact Of Caved Rocks On Stability Of Cylindrical Cavedmentioning
confidence: 83%
“…The analysis process follows the principle that the loose range is the released range [ 30 , 31 ]. Suppose the loosening height of coal body at any time is h t , the vertical distance from coal discharge port to roof is h 0 , the part below h 0 is defined as lower coal body, and the part above h 0 is defined as upper coal body.…”
Section: Schemes and Resultsmentioning
confidence: 99%